Modification of wise pattern based design with free nipple areolar complex graft in a case of juvenile hypertrophy of the breasts (Faculty of Medicine Universitas Indonesia, 2008)
Juvenile hypertrophy of the breast (JHB) is a rare condition leading to gigantomastia unilaterally or bilaterally in peripubertal females. The pathology is limited usually to the breast, with otherwise normal growth and development and without any other deformities. The rapid bilateral or unilateral growth of the breast in adolescent girls leads to severe physical and psychological problems. The etiology remains elusive, but it is believed to represent an end-organ hypersensitivity during a period of intense endocrine regulatory stress. The best treatment is surgical whereas the younger patients better treated with mastectomy to anticipate the high recurrency rate, while older women is best treated with reduction mammaplasty. We report one case of a woman who had a unilateral JHB. The growth of the left breast started in her pubertal age and kept growing for one year. She was treated surgically with Wise pattern based design. After two years, she had no recurrent enlargement and aesthetically, the symmetry of both breasts is achieved with a satisfying scar. (Med J Indones 2008; 17: 13-9)Keywords: juvenile hypertrophy of the breast, reduction mammaplasty, wise pattern based design